Modeling the influence of flight phase control on center of mass trajectory and reaction forces during landing - McNitt-Gray, J. L.; Requejo, P. S.; Flashner, H.; Held, L. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Complex goal-directed human movements consist of a series of phases with multiple objectives. Knowledge of the relationship between control and dynamics during flight and subsequent contact phase is essential for improving landing performance without sustaining injury. The purpose of this study was to 1) model the relationship between the flight phase control, the center of gravity (CG) trajectory and the reaction force during contact with the landing surface and 2) determine how control of the lower extremities prior to contact, as observed experimentally, influences the reaction force during impact.